Yield of peripheral sodium channels gene screening in pure small fibre neuropathy. Issue 3 (15th December 2018) - Eijkenboom, Ivo; Sopacua, Maurice; Hoeijmakers, Janneke G J; de Greef, Bianca T A; Lindsey, Patrick; Almomani, Rowida; Marchi, Margherita; Vanoevelen, Jo; Smeets, Hubertus J M; Waxman, Stephen G; Lauria, Giuseppe; Merkies, Ingemar S J; et al.
Abstract : Background: Neuropathic pain is common in peripheral neuropathy. Recent genetic studies have linked pathogenic voltage-gated sodium channel (VGSC) variants to human pain disorders. Our aims are to determine the frequency of SCN9A, SCN10A and SCN11A variants in patients with pure small fibre neuropathy (SFN), analyse their clinical features and provide a rationale for genetic screening. Methods: Between September 2009 and January 2017, 1139 patients diagnosed with pure SFN at our reference centre were screened for SCN9A, SCN10A and SCN11A variants. Pathogenicity of variants was classified according to established guidelines of the Association for Clinical Genetic Science and frequencies were determined. Patients with SFN were grouped according to the VGSC variants detected, and clinical features were compared. Results: Among 1139 patients with SFN, 132 (11.6%) patients harboured 73 different (potentially) pathogenic VGSC variants, of which 50 were novel and 22 were found in ≥ 1 patient. The frequency of (potentially) pathogenic variants was 5.1% (n=58/1139) for SCN9A, 3.7% (n=42/1139) for SCN10A and 2.9% (n=33/1139) for SCN11A . Only erythromelalgia-like symptoms and warmth-induced pain were significantly more common in patients harbouring VGSC variants. Conclusion: (Potentially) pathogenic VGSC variants are present in 11.6% of patients with pure SFN. Therefore, genetic screening of SCN9A, SCN10A and SCN11A should be considered in patients with pure SFN, independently of clinical features or underlying conditions.